Occupational Segregation and the Gender Wage Gap: Evidence from Ethiopia - Fenet Jima Bedaso (Global Labor Organization (GLO), 2024)
This paper examines the role of female occupational segregation on the gender wage gap across the entire wage distribution. Using the Ethiopian labor force survey, I employ unconditional quantile regression based on the recentered in uence function and correct sample selection issues that arise due to nonrandom decision of female labor force participation using Heckman's two-stage method for baseline estimation. The results show that women earn less than men throughout the wage distribution, even after controlling for personal and labor market characteristics. Importantly, female occupational segregation has a negative coefficient across the wage distribution except at the end of the distribution and partly explains the gender wage gap at the bottom and median percentile of the wage distribution. Using the recentered in uence function decomposition, I find that the gender wage gap due to structural effect is highest at the bottom of the wage distribution, evidence of sticky oor effects. Finally, the estimation shows that the gender wage gap is higher in the private sector than in the public sector across the wage distribution.
Keywords: C21; J3; J16; J71; 330; Occupational segregation; gender wage gap; unconditional quantile regression; Ethiopia